Интерактивный контроль штамповки крупногабаритных листовых деталей - Тараненко, Михаил Евгеньевич (НТУ "ХПИ", 2016)
Обговорены преимущества интерактивного контроля процесса штамповки крупногабаритных листовых деталей. Контролируются формы заготовки в ходе процесса деформирования, величина зазоров между отштамповкой и оснасткой и, в определенной мере, состояние энерговыделяющей системы оборудования. Рассмотрено два метода контроля: с помощью струйных воздушных датчиков и акустический метод контроля. Приведены возможные варианты технических решений расположения датчиков. Методы контроля применимы для штамповки на многокривошипных механических прессах, процессов штамповки эластичной или жидкой средой, а также импульсных (электрогидравлических) методов штамповки указанных деталей. Показаны преимущества и недостатки двух методов.

A large sheet metal parts are parts with dimensions greater than 1.0 m. In most cases, on the surface they are local elements in the form of a rift, cuttings, parts of mating surfaces with small radii of curvature. These sites require for their formation of high pressure or effort compared to the shaping of the general shape of the part. These details are avtokuzovnye panels, mirrors or antennas satellite space communications, details of cladding and lining units aircraft. To assess the ability to control the value of the blank to fit different matrix structure were analyzed and methods for measuring the characteristic distances – potentiometric, capacitive, inductive sensors and optical measurement methods. Main advantages of interactive control of forming of large-dimensional sheet articles are considered. Principal parameters under controlling of forming are blank shape, value of gapping between blank and forming tool and the state of energy-releasing system of equipment. Two controlling methods are analyzed: by means of jet-pipe transducers and acoustic method. Possible methods of engineering solutions of transducers location are shown. Mentioned methods of controlling are applicable for forming of large-dimensional articles on crank mechanical presses, by elastic or liquid mediums and impulse (electro-hydraulic) ones. Advantages and disadvantages of considered controlling methods are revealed.
Interactive controlling of forming of large-dimensional sheet articles
Keywords: листовая штамповка; контроль; струйные датчики; акустический метод контроля; штамповая оснастка; sheet forming; controlling; jet-pipe transducer; acoustic method of controlling; forming tool